Comparative analysis of the diversity within the B. bronchiseptica fimX locus - Tracy L. Nicholson; Sarah M. Shore (PLoS ONE, 2026)
Bordetella bronchiseptica is a highly contagious veterinary bacterial respiratory pathogen with a broad host range that can cause a variety of clinical disease outcomes ranging from asymptomatic carriage to severe pneumonia. B. bronchiseptica fimbriae mediate attachment to respiratory epithelium and are considered to serve as potential protective antigens. Several comparative genomic studies involving B. bronchiseptica strains have demonstrated an overall low level of genomic variability. The region located within the fimX locus is one of the few regions in which genomic variability has been reported. The goal of this study was to comprehensively evaluate the genomic variability harbored within the fimX locus among B. bronchiseptica strains. Our analysis revealed that the genetic variability identified within the fimX locus included both the number of genes harbored, as well as the type of predicted fimbrial subunit gene types contained within the fimX locus. A total of six different fimbrial subunit gene types were identified among the B. bronchiseptica genome assemblies analyzed in this study. Comparative analysis data also suggests that the diversity among the fimbrial subunit genes located within the fimX locus was likely generated by homologous recombination.